The political unconscious of practice theory: Populism and democracy. (June 2020) - Strand, Michael
This article attempts a self-clarification of practice theory by providing a genetic history of 'practice' as a figure in social thought. This locates two different versions of practice theory in Marx's 'practical question' and Hobbes' 'Kingdom of Darkness', respectively, and shows how both historically comprise a practical critique of testing reason. This article examines how the practical critique performs a dialectic of politicization and depoliticization that finds family resemblances and paradoxical alignments between the political left and right. The article evaluates the strength of the practical critique and asks whether it results in a power politics with both left and right versions.